RESEARCH OF INFLUENCE OF QUALITY OF ELECTRONIC EDUCATIONAL RESOURCES ON QUALITY OF TRAINING WITH USE OF DISTANCE TECHNOLOGIES (Journal of Information Technologies in Education (ITE), 2014)
Communication improving of educational processes requires today new approaches to the management arrangements and forming of educational policy in the field of distance learning,which is based on the use of modern information and communication technologies. An important step in this process is the continuous monitoring of the development and implementation of information technology and, in particular, the distance learning systems in higher educational establishments.     The main objective of the monitoring is the impact assessment on the development of distance learning following the state educational standards, curricula, methodical and technical equipment and other factors; factors revelation that influence the implementation and outcomes of distance learning; results comparison of educational institution functioning and distance education systems in order to determine the most efficient ways of its development.     The paper presents the analysis results of the dependence of the quality of educational services on the electronic educational resources. Trends in educational services development was studied by comparing the quality influence of electronic educational resources on the quality of educational services of higher pedagogical educational institutions of Ukraine as of 2009-2010 and 2012-2013.     Generally, the analysis of the survey results allows evaluating quality of the modern education services as satisfactory and it can be said that almost 70% of the success of their future development depends on the quality of the used electronic educational resources and distance learning systems in particular.
Keywords: educational services; quality of training; quality management system; electronic educational resources; quality monitoring; distance learning